2009
DOI: 10.2527/jas.2008-0923
|View full text |Cite
|
Sign up to set email alerts
|

A genome scan for quantitative trait loci affecting male reproductive traits in a White Duroc × Chinese Erhualian resource population1

Abstract: Chinese Erhualian boars have dramatically smaller testes, greater concentrations of circulating androgens, and fewer Sertoli cells than Western commercial breeds. To identify QTL for boar reproductive traits, testicular weight, epididymal weight, seminiferous tubular diameter at 90 and 300 d, and serum testosterone concentration at 300 d were measured in 347 F(2) boars from a White Duroc x Chinese Erhualian cross. A whole genome scan was performed with 183 microsatellites covering 19 porcine chromosomes. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
2
24
1
1
Order By: Relevance
“…A three-generation F 2 population was established by a cross between Chinese Erhualian and White Duroc pigs as described in Ren et al (2008). Briefly, two White Duroc boars and 17 Erhualian sows were mated to produce F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A three-generation F 2 population was established by a cross between Chinese Erhualian and White Duroc pigs as described in Ren et al (2008). Briefly, two White Duroc boars and 17 Erhualian sows were mated to produce F 1 pigs, from which nine F 1 males and 59 F 1 females were intercrossed to produce six batches of 1912 F 2 pigs.…”
Section: Animalsmentioning
confidence: 99%
“…The information content of each marker was more than 0.5. As described previously (Ren et al, 2008), amplification condition for each marker locus was optimized by using standard protocols. After amplifications with primers labeled by fluorescent dyes (NED, FAM or HEX), genotype data were recorded and collected in an ABI PRISM R 3130XL genetic analyzer with GeneMapper TM Genotyping version 3.7 (Applied Biosystems, Foster City, USA).…”
Section: Genotypingmentioning
confidence: 99%
“…In the current study, a suggestive (P b 0.07) association is found with skatole level. ESR1 is located on SSC1p24-25 which is evidence of harbouring several QTL for sperm count and sperm motility (Ren et al, 2009). ESR1 is reported to be a promising candidate gene for boar sperm quality and fertility (Gunawan et al, 2011) and is genetically related to androstenone (Grindflek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Within proximity to the HYAL genes, several QTL have been identified with implications to reproductive traits in swine (Hu et al, 2007). Two ovulation rate QTL (Rathje et al, 1997; Bidanel et al, 2008), an age at puberty QTL (Bidanel et al, 2008), and most recently a QTL for testosterone levels (Ren et al, 2009) have been reported in the same region on SSC13. Interestingly, a SNP within HYAL2 was associated with levels of testosterone and androstenone in Norwegian Landrace boars (Moe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%